2020
DOI: 10.3390/healthcare9010003
|View full text |Cite
|
Sign up to set email alerts
|

Development of Case Numbers during the COVID-19 Pandemic in a Center of Maximum-Care for Traumatology and Orthopedic Oncology

Abstract: (1) Background: The COVID-19 pandemic has led to a significant change in the utilization of trauma surgery and tumor orthopedic hospital facilities. (2) Methods: In a monocentric retrospective analysis, the weekly numbers of cases requiring intra-clinical treatment in the first four months of 2020 were compared with those of 2019. Patients’ visits to the emergency department and shock room, consultation hours, work-related accidents, case numbers in the normal and intensive care units, ventilation hours, the “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“… 16 However, most of the geriatric proximal femur fractures included in this study occurred as the result of minor trauma (95%) and in the home environment (81%) without the direct influence of road traffic. It was observed that during the onset of the COVID-19 pandemic not only the overall number of trauma patients presenting in the emergency room decreased significantly, 14 but also that of patients with heart attacks and strokes. 17 - 20 Nevertheless, it is highly unlikely that geriatric patients with proximal femur fractures would not present in the emergency department as this injury is usually associated with intolerable pain and immobility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 16 However, most of the geriatric proximal femur fractures included in this study occurred as the result of minor trauma (95%) and in the home environment (81%) without the direct influence of road traffic. It was observed that during the onset of the COVID-19 pandemic not only the overall number of trauma patients presenting in the emergency room decreased significantly, 14 but also that of patients with heart attacks and strokes. 17 - 20 Nevertheless, it is highly unlikely that geriatric patients with proximal femur fractures would not present in the emergency department as this injury is usually associated with intolerable pain and immobility.…”
Section: Discussionmentioning
confidence: 99%
“…A marked drop in the overall number of orthopedic outpatients and inpatients was seen during the first phase of the corona pandemic. 13 , 14 Especially among young people, the number of injuries to the upper extremity due to work, sports and traffic accidents decreased due to a reduction in the volume of traffic and suspension of team sports, while injuries caused by accidents in the home increased. 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning surgeries and loco-regional therapies, 106 indicators were identified from 30 articles [42,48–51,55,62,65,65,75,81,90,92–94,97–99,101–103,111,118–125]. Of those, 82 indicators (79%) showed a reduction in the number of treatment procedures, namely in Italy, France, Germany, Ireland, Netherlands, Spain, Turkey, UK, US, Australia, and in 1 international study.…”
Section: Resultsmentioning
confidence: 99%
“…Interessanterweise trifft der Rückgang der Inzidenz nicht auf die „fragility fractures“ und osteoporoseassoziierten Frakturen zu [ 18 ]. Weiterhin zeigt die Literatur einen Rückgang der Arbeitsunfälle und polytraumatisierter Patienten in Pandemiezeiten [ 13 , 14 ].…”
Section: Introductionunclassified